Why small-scale fuel ethanol production in Brazil does not take off?. (March 2015) - Mayer, Flávio Dias; Feris, Liliana Amaral; Marcilio, Nilson Romeu; Hoffmann, Ronaldo
Abstract: Ethanol production on small scale (on-farm) substantially contributes to the effort to replace fossil fuels. However, the share of small scale production remains incipient, either due to inefficiency in the process or legal restrictions on the commercialization of hydrous ethanol fuel. The aim of this paper is to justify this incipient industry by detailing the small-scale ethanol production process and presenting operational data collected in the literature from the last three decades. The reviewed data showed that the inefficiency of the process affects the economic feasibility by product losses in bagasse and vinasse or through excessive energy consumption. The feasibility of ethanol production on small scale requires addressing these technological obstacles through the integral use of co-products.